The Parent-Child Relationship: A Psychological Perspective - Rahul Vasant Savdekar; Prof. Dr. M. D. Autade (International Journal of Indian Psychȯlogy, 2025)
The parent-child relationship is a fundamental aspect of human development, profoundly influencing a child’s psychological, emotional, and social well-being. This study explores the dynamics of this relationship through a psychological lens, focusing on factors such as attachment styles, parenting techniques, and their effects on the child’s growth and behavior. By analyzing key theories, empirical studies, and cultural variations, this research provides insights into how nurturing or dysfunctional relationships shape an individual’s mental health and interpersonal skills. Additionally, the study examines contemporary challenges, including the impact of technology and changing family structures, offering recommendations for fostering healthy parent child bonds.